Solution of nonlinear integral equations via fixed point theorems in G-metric spaces - Rashwan, Rashwan; Saleh, Samera (International Journal of Applied Mathematical Research, 2014)
The main aim of this paper is to prove that the existence and uniqueness of solutions for systems of simultaneous Volterra Hammerstein and Urysohn nonlinear integral equations in G-metric spaces and partially ordered G-metric spaces settings by using common fixed point theorems satisfying generalized contractive conditions.